Web application vulnerabilities detect, exploit, prevent - Cross, Michael, 1965- (Burlington, MA : Syngress Pub., 2007)
In this book, we aim to describe how to make a computer bend to your will by finding and exploiting vulnerabilities specifically in Web applications. We will describe common security issues in Web applications, tell you how to find them, describe how to exploit them, and then tell you how to fix them. We will also cover how and why some hackers (the bad guys) will try to exploit these vulnerabilities to achieve their own end. We will also try to explain how to detect if hackers are actively trying to exploit vulnerabilities in your own Web applications. Learn to defend Web-based applications developed with AJAX, SOAP, XMLPRC, and more. See why Cross Site Scripting attacks can be so devastating. Download working code from the companion Web site.
Chapter 1: Introduction -- Chapter 2: Information Gathering Techniques -- Chapter 3: Common Input Validation Vulnerabilities -- Chapter 4: Application Logic Flaws and Common Coding Issues -- Chapter 5: Common Client Trust Issues -- Chapter 6: Server Side Validation Vulnerabilities in a Multi User Multi Role Environment -- Chapter 7: Session Management Vulnerabilities -- Chapter 8: Phishing -- Chapter 9: Client Side Security -- Chapter 10: Same Issues / New Technologies -- Chapter 11: Other Security Considerations.
Includes index.
Keywords: Application software -- Security measures; Computer security; Electronic books